Development of a risk management framework for the petroleum supply chain in South Africa - Ajayi, Oluyomi Babafemi (My University, 2016)
Energy supply is the backbone of almost all economic activities, powering critical systems and infrastructures required for the functioning of our modern economies and societies. Regardless of where and how they are produced, energy must be delivered to the points of consumption and any disruptions in the chain can rapidly cascade into a national crisis. However, sustaining an undisrupted production and supply of this vital resource has been identified as a major challenge globally with issues like terrorism, spiralling and unstable energy prices, technology uncertainties and natural disasters posing serious threats to the supply chain. Of the identifiable energy supply chains, this study develops a risk management framework for the petroleum supply chain using discrete event modelling and simulation techniques. Within the framework is a risk simulation software for OILREF’s petroleum supply chain which gives a reliable estimate of the health of the critical path in the chain, triggers exceptions, reduces decision making cycle times and improves quality of risk decisions across the chain with online monitoring and reporting of pre-defined risk drivers.